Construction of Cryptographically Strong S-Boxes Inspired by Bee Waggle Dance - Isa H.; Jamil N.; Zaba M.R. (Springer Tokyo, 2023)
Cryptography; Bee Algorithm; Bee Waggle Dance; Box construction; Power functions; Substitution boxes; Heuristic methods